Students’ Perception of History Learning Methods in Class X SMA Negeri 15 Semarang - Dhani, Muhammad Iqbal; Atno, Atno (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This study aims to explore the perceptions of Grade X students at SMA Negeri 15 Semarang regarding various history teaching methods used in class, including lectures, group discussions, the use of digital media, and project-based approaches. This research employs a qualitative exploratory approach, with data collected through student questionnaires and semi-structured interviews with history teachers. The findings show that most students perceive the dominant lecture method as monotonous, boring, and lacking interactivity. In contrast, teaching methods that actively involve students—such as group discussions, presentations, historical videos, interactive maps, and educational applications—received positive responses. These approaches were considered more engaging, easier to understand, and better suited to the learning styles of the digital generation. These findings highlight the importance of innovation in history teaching methods that are more contextual, participatory, and technology-integrated to enhance both the effectiveness and meaningfulness of learning. This study contributes to understanding student perceptions as a foundation for developing more relevant and enjoyable history teaching strategies.